Approaches used by parents to keep their children safe at home: a qualitative study to explore the perspectives of parents with children aged under five years - Ablewhite, Joanne; McDaid, Lisa; Hawkins, Adrian; Peel, Isabel; Goodenough, Trudy; Deave, Toity; Stewart, Jane; Watson, Michael; Kendrick, Denise (BioMed Central, 2015)
BACKGROUND: Childhood unintentional injury represents an important global health problem. Many unintentional injuries experienced by children aged under 5years occur within the home and are preventable. The aim of this study was to explore the approaches used by parents of children under five in order to help prevent unintentional injuries in the home and the factors which influence their use. Understanding how parents approach risk-management in the home has important implications for injury practitioners.